2015
DOI: 10.1523/eneuro.0049-15.2015
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibitory Plasticity Permits the Recruitment of CA2 Pyramidal Neurons by CA3

Abstract: Area CA2 is emerging as an important region for hippocampal memory formation. However, how CA2 pyramidal neurons (PNs) are engaged by intrahippocampal inputs remains unclear. Excitatory transmission between CA3 and CA2 is strongly inhibited and is not plastic. We show in mice that different patterns of activity can in fact increase the excitatory drive between CA3 and CA2. We provide evidence that this effect is mediated by a long-term depression at inhibitory synapses (iLTD), as it is evoked by the same proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 31 publications
(56 reference statements)
3
64
0
Order By: Relevance
“…We have recently shown that a HFS in SR induces an iLTD in area CA2 that results in a large increase in the depolarizing component of the PSP amplitude evoked by SC stimulation (Nasrallah et al, 2015). We asked whether the plasticity of inhibitory transmission that we can induce with a distal input HFS could be sufficient to modulate the level of excitatory drive at SLM-CA2 synapses.…”
Section: Hfs In Slm Induces Iltd and Alters The Excitatory/inhibitorymentioning
confidence: 97%
See 3 more Smart Citations
“…We have recently shown that a HFS in SR induces an iLTD in area CA2 that results in a large increase in the depolarizing component of the PSP amplitude evoked by SC stimulation (Nasrallah et al, 2015). We asked whether the plasticity of inhibitory transmission that we can induce with a distal input HFS could be sufficient to modulate the level of excitatory drive at SLM-CA2 synapses.…”
Section: Hfs In Slm Induces Iltd and Alters The Excitatory/inhibitorymentioning
confidence: 97%
“…We have recently shown that inhibitory synapses recruited in SLM express an activity-dependent hetero-synaptic LTD following HFS of proximal inputs (Nasrallah et al, 2015). We investigated whether iLTD of distal CA2 inputs could also be induced homo-synapticaly by HFS in SLM.…”
Section: Hfs In Slm Induces Iltd and Alters The Excitatory/inhibitorymentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, feedforward recruitment of CA2 inhibitory interneurons was identified to underpin this "delay-relay." Furthermore, longterm depression of the excitation of CA2 inhibitory interneurons permitted distal excitation of CA2 pyramidal neurons, allowing them to fire and relay activity to CA1 (Nasrallah et al 2015). The significance of CA2 and its connections was recently highlighted as critical for social memory (Hitti and Siegelbaum 2014;Stevenson and Caldwell 2014) and in a mouse model of schizophrenia where CA2 is functionally disconnected from the trisynaptic pathway by excessive feedforward inhibition (Piskorowski et al 2016).…”
Section: Circuit-level Voltage Imaging Approachesmentioning
confidence: 99%